A Critical Study on Real Number System - Pralay Poria (Mathematical Statistician and Engineering Applications, 2022)
Mathematically a number is used for counting and measuring. A notational symbol which represents a number is called a numeral, but in common usage the word number is used for both the abstract object and the symbol, as well as for the word for the number. In mathematics, the definition of number has been extended over the years to include such numbers as zero, positive numbers, negative numbers, rational numbers, irrational numbers and complex numbers.